2020
DOI: 10.18805/ijare.a-481
|View full text |Cite
|
Sign up to set email alerts
|

Germination Capacity of Annona deceptrix (Westra) H. Rainer (Annonaceae) an Endemic and Endangered Species in Manabí, Ecuador

Abstract: Annona deceptrix is an endemic and endangered tree from Ecuador according to the IUCN Red List of Endangered Species™. Its endangered status has been related with anthropogenic activities and some intrinsic characteristics of this species such as a low germination capacity of its seeds under natural conditions which is a serious limitation to obtain plants to establish conservation and breeding strategies. The objective of this study was to determine the seed germination capacity of A. deceptrix under differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…MGT is a useful parameter to evaluate a species occupation speed in a location. Our finding (MGT > 10 days) shows that araticum can be classified as a reasonably slow species (PICO-MENDOZA et al, 2020).…”
Section: Resultsmentioning
confidence: 54%
“…MGT is a useful parameter to evaluate a species occupation speed in a location. Our finding (MGT > 10 days) shows that araticum can be classified as a reasonably slow species (PICO-MENDOZA et al, 2020).…”
Section: Resultsmentioning
confidence: 54%
“…Other studies have also indicated that the application of different GA 3 concentrations has no effect on seed germination (Pico-Mendoza et al, 2020). However, Saldivar-Iglesias et al (2010) found that higher concentration of GA 3 increased the germination percentage (87%) in Jaltomata procumbens (Cav.)…”
Section: Effect Of Gibberellic Acid On Seed Germination Capacity and ...mentioning
confidence: 97%